Evaluación de la calidad del servicio de la dirección de agua potable y su relación con la satisfacción ciudadana en el municipio de el empalme, año 2024 - Solórzano Intriago, María Mercedes (2025)
The objective of this research is to evaluate the relationship between the quality of customer service provided by the Drinking Water Directorate and citizen satisfaction in the Municipal GAD of El Empalme canton, during the year 2024. The study was conducted using a qualitative-quantitative methodological approach, classified as exploratory, descriptive, and bibliographic research. Descriptive, inductive, deductive, and statistical methods were employed. The research population consisted of users who make use of the services provided by this municipal department, with a representative sample of 382 surveys defined. Additionally, an interview was conducted with the representative of the Drinking Water Directorate of the Municipal GAD of El Empalme canton. The research results revealed a direct relationship between operational deficiencies and citizen satisfaction: the combined analysis of the interview and the survey shows that the Drinking Water Directorate in El Empalme faces structural and operational challenges that limit the perceived quality of service. Although there are institutional efforts to improve, these are not always perceived by users. The most critical areas are tangibility, reliability, and empathy, while responsiveness and security show moderate progress but still offer opportunities for improvement. These findings lead to the conclusion that strategic interventions are needed, particularly in the modernization of infrastructure and technical equipment, improvement of internal communication, and strengthening of human talent competencies. It is recommended to modernize technology, digitize internal processes to speed up service, and implement personalized service mechanisms. Additionally, it is essential to reinforce staff training in customer service and empathy, as well as to develop more effective communication channels to strengthen the relationship with users.